Model kebijakan pengembangan sistem pertahanan sosial berbasiskan modal sosial masyarakat di daerah perbatasan - Asrinaldi Asrinaldi; Yoserizal Yoserizal (Masyarakat, Kebudayaan dan Politik, 2014)
A threat against the state is no longer in the forms of conventional war declarations or weaponary; but rather in the form of the loss of nationalism spirit due to the waning of national identity in a country. Along with the development of globalization, there is a shift regarding the threats against the state sovereignty. In Batam, Riau Province, as the border area, the threats include economic inequality between communities, the impact of trade liberalization, transnational crime, and the loss of collective identity due to the influence of globalization values using a qualitative approach, this article finds out that there are two forms of community respones related to social defense system; active and passive respones. However, in general, people in the border area in Batam respond more passively so that it affects the formation of the society defense system. In addition, this study also finds out that there are three stages in the formation of social defense system that can be used as a basis in policy formulation model for social defense system, including perception, togetherness, identification of collective action, as well as networking proliferation and regional integration.